Magnetic resonance imaging features of complications following hip replacement: A pictorial review - Pilania, Khushboo; Jankharia, Bhavin (Indian Journal of Radiology and Imaging, 2016)
Hip replacement surgery helps millions of people worldwide walk painlessly each year. With increasing life spans and decreased clinical threshold for surgery, this number will continue to rise. With the increase in the number of surgeries and the longevity of implants, the need for early and prompt diagnosis of complications is also rising. This essay underlines the fact that magnetic resonance imaging on a 1.5T scanner with specialized metal artefact reduction sequences is a viable technique to image the post-arthroplasty hip and has vast potential in the prompt and early diagnosis of complications in these patients.
Keywords: Arthroplasty hip; artifacts; complications; magnetic resonance imaging; musculoskeletal abnormalities